A inclusão de pessoas com deficiência nas organizações: uma abordagem integral baseada na espiritualidade - Veríssimo, Magda Silvia Berté (Universidade do Vale do Rio dos Sinos, 2017)
The present research seeks an understanding about the process of including people with disability in the organizational environment, considering all its historical aspects involving the meaning of the concept, which reflects on the current understanding. Mainly because of labor laws’ recent requirements – Lei de Cotas, regulated in 1991, which involves the entrepreneurs to fill a quota of people with disability in the organizational environment. Since then, companies have been through difficult periods. The majority do not comply with the current regulation, and end up suffering several penalties. All of the inclusion movements’ accomplishments, the advanced studies about people with disability’s rights and the main difficulties for society to promote a real inclusion in the market place make it obvious how far we are from getting to a more diverse workplace. The discussion whether to make companies fully responsible for complying with this regulation as well as educating their employees to be more thoughtful is fairly new; after all, the work environment is not only meant for a job, but also for developing empathetic human beings. Due to this new regulation, a spontaneous engagement by some companies and their employees can be noticed. This involvement does not echo responds as quickly as the market dynamic of people with disability and the labor law need. Thus, the moment to propose a new way to promote inclusion effectively has arrived. It has been identified, within the theory of Integral Approach and the spirituality in the workplace, the crucial concepts to promote an organizational environment that develops conscious and engaged people in this matter. Additionally, spirituality in the workplace provides the appropriate atmosphere to encourage individual connections, once its concepts contemplate people’s development through the awareness and connectivity with themselves and others. Through theoretical findings, an empirical research was performed, based on a semi-structured interview script, with approximately forty participants, representing large companies from Porto Alegre area. Amongst the participants, there were leaders, peers of people with disability, people with disability themselves and HR representatives in each company. Every organization involved in the present research had initiatives to promote inclusion of people with disability, but not necessarily a formal program. The findings have provided a comprehensive understanding of the current diversity scenario in the organizational environment as well as have offered a different possibility of promoting it, which suggests a new way of seeing the subject. Firstly, with the action of the main agents involved in the cause, individuals and companies start developing people to build a more inclusive society: through a model of inclusion named integral.
Keywords: Inclusão de pessoas com deficiência; Abordagem Integral; Espiritualidade nas organizações; Inclusion of people with disability; Integral approach; Spirituality in the workplace; ACCNPQ::Ciências Sociais Aplicadas::Administração